Developing a Visual Attention Assessment for Children at School Entry - Prieler, Tanja; Wood, Clare; Thomson, Jenny M. (Frontiers in Psychology, 2018)
Whereas young children’s visual attention has been explored in a number of previous studies, so far it has not been investigated by an assessment based on Bundesen’s Theory of Visual Attention (TVA). TVA , is a prominent visual attention model that has been widely used as foundation in studies targeting older children, adolescents or adults. In this paper we explore the utility of adopting TVA to explore the visual attention of 4- to 5- year olds and present the development of a simplified adapted version of a TVA-based assessment designed for this age group. Key assessment alterations included the substitution of letter stimuli with black and white symbols and the reduction of assessment duration. The suitability of the assessment for the target age group was subsequently tested in two consecutive studies (Study I: N = 43; Study II: N = 24). Study results show that measuring visual attention based on a simplified TVA-based assessment appears feasible in such a young age group, provided that the study design takes into account the capabilities of these young children. The authors argue that by adopting this kind of visual attention assessment the relationship between visual attention development and early learning could be better understood.